PENGARUH KEPUASAN KERJA, KOMITMEN ORGANISASIONAL DAN KARAKTERISTIK PEKERJAAN TERHADAP KINERJA KARYAWAN (Studi Pada PT. Mitra Saudara Indosengon (MSI) Kendal ) (Students' Journal of Economic and Management, 2012)
Target of this research to test and analyze influence satisfaction of job, organizational commitment and work characteristic to employees performance at PT. Mitra Saudara Indosengon (MSI) Kendal.Pursuant to the description hence this research take title “Pengaruh Kepuasan Kerja, Komitmen Organisasional Dan Karakteristik Pekerjaan Terhadap Kinerja Karyawan (Studi Pada PT.Mitra Saudara Indosengon (MSI) Kendal )”. Research concerning influence satisfaction of job, organizational commitment and work characteristic to employees performance at PT. Mitra Saudara Indosengon (MSI) Kendal taking sample counted 100 responder. In this research use obtained primary data with questioner. As for data analysis use regression analysis. Pursuant to result of research of satisfaction of job have an effect on positive and significant to employees performance. Employees PT. Mitra Saudara Indosengon (MSI) Kendal have lick lips, this matter is seen fromresponder answer mean which replying agree. Organizational Commitment have an effect on positive and significant to employees performance. Employees PT. Mitra Saudara Indosengon (MSI) Kendal to company still enough, this matter is seen from responder answer mean which replying is neutral. Work characteristic have an effect on positive and significant to employees performance. Work executed by PT. Mitra Saudara Indosengon (MSI) Kendal have according to its membership, this matter is seen from responder answer mean which replying agree. Equal to 55,2 % can be explained by satisfaction of job, organizational commitment and work characteristic to employees performance. While the rest 44,8% explained by other causes outside variable satisfaction of job, organizational commitment and work characteristic like motivation, leadership, environmental of job, training and education.Keywords : Satisfaction of Job, Organizational Commitment, Work Characteristic And Employees Performance.